Labor History amid the Cultural and Linguistic Turns in Philippine Historiography: An Anti-Nationalist Critique (Recoletos Multidisciplinary Research Journal, 2025)
Between 1959 and 1985, only seven studies on the Philippine labor movement were made due to security risks under the Marcos dictatorship. With the fall of the martial law regime in 1986, an upsurge in labor history was witnessed with the vigorous publication of studies on the history of Filipino workers and their labor movement. This paper explored the defining characteristics of labor history in the Philippines by surveying at least fifteen books and articles on Philippine labor published from 1988 to 1998. The literature then was contextualized to the cultural and linguistic turns that took over Philippine historiography after 1986, which in turn was critiqued by adopting an anti-nationalist perspective. The results show that these works can be categorized as ?old labor history? in their tradition and were individual in nature due to the absence of collaboration attempt between historians and social scientists. Furthermore, labor history declined at the turn of the twenty-first century as the indigenization movement, particularly Pantayong Pananaw, dramatically shifted the academic focus from political economy towards the study of Philippine languages and culture.
Keywords: indigenization; labor history; labor movement; Pantayong Pananaw; Philippine historiography